An evaluation of parent implemented web‐based behavioral skills training for firearm safety. (23rd July 2020) - Novotny, Marissa A.; Miltenberger, Raymond G.; Frederick, Katelyn; Maxfield, Trevor C.
Abstract: Behavioral skills training (BST) is effective for teaching safety skills but often requires a behavior analyst to conduct the training, which can make it costly and inaccessible for most parents. Parent‐conducted BST may allow for children to receive training without the need for a trained behavior analyst. Manualized training from a website could allow parents access to needed material at a low cost. This study evaluated a web‐based manualized intervention implemented by parents for teaching firearm safety skills using BST. We used a multiple‐probe across participants design to assess the effectiveness of parent‐conducted BST. Results indicate that three children acquired the safety skills after parent‐conducted BST alone, and the other three children required experimenter‐conducted IST.